Structural study of W2B obtained via mechanical alloying of W, B4C, TiC and graphite before and after He ions irradiation. (June 2022) - Neov, D.; Slavov, L.; Donkov, A.A.; Mirzayev, M.N.; Popov, E.; Demir, E.; Siemek, K.; Djourelov, N.; Turchenko, V.A.; Sharipov, Z.A.; Horodek, P.; Beskrovnyi, A.I.; et al.
Highlights: W 6wt.%B4 C 2wt.%TiC 1wt.%C weight ratio is used in mechanical alloying process. Sintering at 2550 °C produces nearly single-phase W2 B (∼98%), WB and TiC (<2%). Irradiation with 2.5 MeV helium ions to a fluence of 5.0 × 10 20 ion/cm 2 is performed. Irradiation has negligible effect on the W2 B main phase content. All trapped He atoms are found to be located in boron vacancy positions in W2 B and WB. Abstract: Elemental powders of W, B4 C, TiC and C (graphite) in percentage weight ratio of W-–6 wt% B4 C–2 wt% TiC–1 wt% C are used as precursors in mechanical alloying process aimed at producing tungsten-based material. The composition of the obtained material is nearly single-phase W2 B (∼98%) with small additions of WB and TiC (<2%), unveiled by XRD analysis. Irradiation with 2.5 MeV helium ions to a fluence of 5.0 × 10 20 ion/cm 2 was performed and the induced radiation damage was assessed. The XRD data unveiled reduction in size of the grains from 300 nm to 260 nm upon the irradiation. It is observed that the irradiation had negligible effect on the W2 B phase content, while the WB phase content increased by 0.74% and TiC phase content decreased with 0.71% upon irradiation. Raman spectral analysis showed that not only graphite's carbon is affected by the irradiation, but also the titanium bonded carbon in TiC underwent changes, resulting in development of non-stoichiometric TiC. Positron annihilation spectroscopy is employed for investigating the presence of intrinsic defects and their evolution upon irradiation. Based on the analysis of all the obtained results, we contemplate that the detected WB phase most probably belongs to the grain boundaries of W2 B grains. The irradiation to a fluence of 5.0 × 10 20 ion/cm 2 did not cause chemical interaction of tungsten boride phases with the carbon species of the material, which would have resulted in the appearance of new phases.